Microwave-mediated Newman-Kwart rearrangement in water - Hoffmann, Ina; Schatz, Jürgen (RSC Advances, 2016)
For the first time the unimolecular Newman-Kwart rearrangement is performed in pure water. The elevated temperatures required for the 1,3-aryl shift are easily accomplished by microwave irradiation. Differently functionalized substrates underline the expected influence on the reaction rate regarding the electronic and steric effects of the substituents. The utilization of supramolecular additives enables an increase in conversion. Besides, the conduction in a microwave reactor allows for a rapid collection of kinetic data affording the reaction rate constants of the rearrangement of distinct substrates as well as the Arrhenius constant and activation parameters of the conversion of 2- and 4-nitrophenyl-O-thiocarbamate.
Keywords: Green chemistry; physical organic chemistry; water